2019
DOI: 10.1097/md.0000000000017001
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant bilateral acute retinal necrosis complicated with secondary herpes simplex type-1 viral encephalitis

Abstract: Rationale:Acute retinal necrosis (ARN), which is characterized by peripheral necrotizing retinitis, severe retinal arteritis, and progressive inflammatory reaction in the vitreous and anterior chambers, has been reported in cases with herpes simplex encephalitis (HSE). It is a relatively rare complication secondary to HSE. However, cases presented with viral encephalitis following ARN were seldom reported.Patient concerns:A 43-year-old immunocompetent male patient manifested the aforesaid reverse situation. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This case is significant due to the very few documented accounts of HSV infection spreading from ARN to the brain. 12 , 15 Our literature review revealed four previous cases of patients who developed acute retinal necrosis due to HSV-1 and later went on to develop CNS infection. Three of the cases were found to have positive HSV-1 PCR testing on both vitreous and CSF samples, one of which was found on post-mortem testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case is significant due to the very few documented accounts of HSV infection spreading from ARN to the brain. 12 , 15 Our literature review revealed four previous cases of patients who developed acute retinal necrosis due to HSV-1 and later went on to develop CNS infection. Three of the cases were found to have positive HSV-1 PCR testing on both vitreous and CSF samples, one of which was found on post-mortem testing.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 The fourth case report had positive HSV-1 PCR testing of a vitreous sample, however there was no mention of CSF PCR HSV testing. 15 Three of these patients had been receiving systemic steroids and one was chronically immunosuppressed.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there is no reported case in the literature of ARN with or without meningitis/encephalitis as a first presentation of an HSV-1 infection. A recent case report has been published describing a rare presentation in a patient who first was diagnosed with ARN and posteriorly with encephalitis, but the authors do not specify if it represents a primoinfection 6…”
Section: Discussionmentioning
confidence: 99%
“…[22] Transmission of the virus from the brain to the eye and reactivation of a latent virus from the frontotemporal lobe and the optic chiasm is a presumed possible mechanism. [23][24][25] A study done on experimental models shows that a reverse mechanism from eye to brain is also possible. In these cases, the virus spreads from the affected eye to the central nervous system along the parasympathetic nerve fibres of the oculomotorius and HSV encephalitis develops within a few days after ARN.…”
Section: Epidemiological Datamentioning
confidence: 99%